Enhanced Optical Fiber for Distributed Acoustic Sensing beyond the Limits of Rayleigh Backscattering - Paul S. Westbrook; Kenneth S. Feder; Tristan Kremp; Eric M. Monberg; Hongchao Wu; Benyuan Zhu; Lei Huang; Debra A. Simoff; Scott Shenk; Vincent A. Handerek; Mohammad Karimi; Anthony Nkansah; et al. (iScience, 2020)
Summary: We report on engineered fibers with enhanced optical backscattering that exceeds Rayleigh scattering limits by more than one order of magnitude. We measure attenuation less than 0.5 dB/km from 1,300 to 1,650 nm. By controlling the enhanced backscatter over a 1.5-km length, we compensate for this attenuation, resulting in a higher backscatter signal at the end of the fiber. We demonstrate that the scattering strength may be stabilized for operation at temperatures above 200°C for at least 3 weeks. We show that the deleterious signal distortion due to the Kerr nonlinearity is within 10% of standard fiber. We then report on the use of these fibers in distributed acoustic sensing (DAS) measurements. A significant increase in acoustic signal-to-noise ratio leads to the possibility of improved spatial resolution in the enhanced fiber DAS system.